Intersectional Solidarity: We Are All the United Nations - Rebecca Adami (UN Chronicle, 2025)
In this article, I suggest that it was thanks to the intersectional solidarity between women with experiences of injustices caused by the Second World War, fascism and colonialism that today we truly have a Universal Declaration of Human Rights. We can carry their legacy further by enacting this call in solidarity with each other, regardless of what separates us and in recognition of what unites us—such as living on a planet facing environmental emergency and the effects of war—as members of the human family.
Worldwide